Obsession In Duncan Jones's Source Code (2011): A Psychoanalytic Approach - Choirunisak, Fatma Sari (2012)
The major problem of this study is how obsession is reflected in Colter Stevens's personality. The objective of this study are to analyze the movie based on structural element and to analyze obsession in Duncan Jones's Source Code based on psychoanalytic approach. This study is literary study, which can be categorized into a descriptive qualitative study. The object of this study is Source Code, a movie by Duncan Jones. The data sources are primary and secondary data sources. The primary data sources is the movie itself, Source Code, and the secondary data sources are related to the primary data that support the analysis such as some books of psychology and website related to the research. The technique of data analysis is descriptive qualitative analysis. The result of this study shows that; firstly the structural elements of the movie consist of character and characterization, setting, point of view, theme, plot, casting, mise-en-scene, cinematography, editing, and sound. Secondly, the psychoanalytic analysis of this movie shows that the obsession of Colter Stevens is to find the bomb and the bomber, he also has big obsession to save all passengers in the commuter train.